Analysis of Snail-1, E-cadherin and claudin-1 expression in colorectal adenomas and carcinomas - Bezdekova, Michala; Brychtova, Svetlana; Sedlakova, Eva; Langova, Katerina; Brychta, Tomas; Belej, Kamil (International journal of molecular sciences, 2012)
We report the expression of Snail-1, E-cadherin and claudin-1 by indirect immunohistochemistry in colonic neoplasia. Snail-1 is a zinc finger transcription factor expressed in cells that already have undergone almost complete epithelial-mesenchymal transition (EMT) and have already evaded from the tumor. The main mechanism by which Snail induces EMT is downregulation of E-cadherin, of which expression was shown to be frequently downregulated in many different types of tumors, where it accompanies the invasiveness and metastatic behavior of malignant cells. Moreover, Snail-1 may downregulate the expression of claudin-1, a cell-cell adhesion protein which plays a likely role in progression and dissemination during tumorigenesis. Snail-1 was expressed in both carcinoma and adenoma cells with histologically normal epithelium in the mucosa, adjacent to the tumors, without significant differences, and predominant strong intensity of staining. Statistically significant differences were revealed between normal and tumorous epithelium (p = 0.003) at the subcellular level, where the shift of the protein to the cytoplasm with combined cytoplasmic/nuclear or pure cytoplasmic expression was observed. E-cadherin expression was present in 100% of cases of both adenocarcinomas and adenomas, with prevailing strong membranous immunoreactivity and no differences between protein expression in tumors and normal mucosa. Predominating strong positivity of claudin-1 was detected in tumor cells of adenocarcinomas and adenomas. Marked differences were seen in protein localization, where membranous staining, typical for nontumorous epithelium, changed to combined membranous/cytoplasmic expression in adenocarcinomas (p = 0.0001) and adenomas (0.0002), in which cytoplasmic shift was associated with a higher degree of dysplasia. Furthermore, membranous/cytoplasmic localization was more frequent in the carcinoma group (87%) in comparison with adenomas (51%) (p = 0.0001). We conclude that dystopic subcellular localizations of Snail-1 and claudin-1 may participate in changes of cellular morphology and behavior which might be associated with altered effectory pathways of proteins and thus substantially contribute to the cancer development.
Keywords: Carcinoma; regulace genové exprese u nádorů; nádorové proteiny; Humans; epitelo-mezenchymální tranzice; Transcription Factors; Cadherins; rodina transkripčních faktorů Snail; Female; Snail-1; E-cadherin; claudin-1; adenocarcinoma; lidé; Epithelial-Mesenchymal Transition; Claudin-1; karcinom; ženské pohlaví; kolorektální nádory; Male; adenom; kadheriny; Adenoma; immunohistochemistry; transkripční faktory; Snail Family Transcription Factors; Neoplasm Proteins; mužské pohlaví; Gene Expression Regulation, Neoplastic; adenoma; Colorectal Neoplasms